Electromagnetic Actuation and Sensing in Medical Robotics (Series in BioEngineering,, 2018)
This book highlights electromagnetic actuation (EMA) and sensing systems for a broad range of applications including targeted drug delivery, drug-release-rate control, catheterization, intravitreal needleless injections, wireless magnetic capsule endoscopy, and micromanipulations. It also reviews the state-of-the-art magnetic actuation and sensing technologies with remotely controlled targets used in biomedicine.